Make the phone work for you - Gellespie, Jack; Moore, Ed; Communication Briefing (Blackwood, N.J. : Communication Briefing, 1991)
This video provides telephone tactics you can use to end phone frustations so you can get more done, srve your customer better and sell more products and services. You'll get practical ideas you can use right away to make the phone work for you.
Copy available in DVD format
Presenter: Ed Moore and Patricia Walker
Keywords: Telephone etiquette; Communications